Relevansi Pendekatan Semantik Toshihiko Izutsu dalam Menafsirkan Al-Qur’an - Suwarno, Suwarno; Soleh, Rahmat; Handayani, Ikrimah Retno (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2022)
The study of the Qur'an is not only an important concern for Muslims, but the Qur'an has also attracted the attention of orientalists in interpreting it using various approaches, one of which is the semantic approach carried out by Thoshihiko Izutsu. This paper discusses the relevance of Toshihiko Izutsu's semantic approach in interpreting the Qur'an. The method used in this paper is a literature research methodology by referring to writings related to the discussion theme. This paper concludes that Toshihiko Izutsu's semantic approach is quite relevant to the needs of contemporary interpretation. Because Toshihiko contains a new view in the Qur'anic world (weltanscuung) so that he can explain things that are sometimes complicated to be simpler through explanations from a review of their relational meanings. In the end, this semantic approach can be used but not for all vocabulary in the Qur'an, the study must also be precise and in-depth, it cannot be arbitrary in understanding the meaning of a vocabulary in the Qur'an